Critiques of Modern Consumerism in the Qur’an: A Study to the Concepts of Israf and Tabdhir in Tafsir al-Wajiz - Khoirunnisa, Asmahan Hasna; Rha’in, Ainur (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2025)
Consumerism that influences modern society has social, psychological, and spiritual implications. The Qur'an as the main source of Islamic teachings contains verses that condemn excessive lifestyles and waste of wealth. This study aims to examine the concept of consumerism through the study of isrāf and tabdzīr in the perspective of the Qur'an. This study uses a qualitative approach based on literature with the thematic interpretation method (maudhu'i), by collecting verses related to consumption (QS. Al-Isra' [17]: 26-27, QS. Al-A'raf [7]: 31, and QS. Al-Furqan [25]: 67), then analyzing them based on the explanations in Tafsir Al-Wajiz by Wahbah Az-Zuhaili and related to the perspective of Islamic psychology. The results of this study indicate that the Tafsir Al-Wajiz emphasizes the prohibition of excess (isrāf), condemnation of wastefulness (tabdzīr), and the importance of an afterlife orientation in consumption practices. The novelty of this study lies in the use of the Tafsir Al-Wajiz compiled using the tahlili method as the main reference in the thematic analysis of consumption verses, as well as its integration with an Islamic psychological perspective to interpret the impact of modern consumerism. Thus, this study offers a balanced and applicable Qur'anic consumption paradigm as a critique of the consumptive lifestyle. Konsumerisme yang mempengaruhi masyarakat modern memiliki dampak sosial, psikologis, dan spiritual. Al-Qur'an sebagai sumber utama ajaran Islam mengandung ayat-ayat yang menentang gaya hidup berlebihan dan pemborosan harta. Penelitian ini bertujuan untuk mengkaji konsep konsumerisme melalui kajian isrāf dan tabdzīr dalam perspektif Al-Qur'an. Penelitian ini menggunakan pendekatan kualitatif berbasis kepustakaan dengan metode tafsir tematik (maudhu'i), yaitu menghimpun ayat-ayat yang berkaitan dengan konsumsi (QS. Al-Isra' [17]: 26-27, QS. Al-A'raf [7]: 31, dan QS. Al-Furqan [25]: 67), kemudian penggunaannya berdasarkan penjelasan dalam Tafsir Al-Wajiz karya Wahbah Az-Zuhaili dan dikaitkan dengan perspektif psikologi Islam. Hasil penelitian ini menunjukkan bahwa Tafsir Al-Wajiz menegaskan larangan isrāf, kecaman terhadap pemborosan (tabdzīr), dan pentingnya orientasi akhirat dalam praktik konsumsi. Kebaruan penelitian ini terletak pada penggunaan Tafsir Al-Wajiz yang disusun dengan metode tahlili sebagai rujukan utama dalam analisis tematik ayat-ayat konsumsi, serta integrasinya dengan perspektif psikologi Islam untuk menafsirkan dampak konsumerisme modern. Dengan demikian, penelitian ini menawarkan paradigma konsumsi Al-Qur'an yang seimbang dan aplikatif sebagai kritik terhadap gaya hidup konsumtif.